Pengaruh Suplementasi Infusa Daun Sirih (Piper betle L.) terhadap Kualitas Telur Puyuh - Fensa Eka Widjaya; Yuli Retnani; Widya Hermana (Institut Pertanian Bogor, 2018)
Natural feed additive supplementation could lead to higher production performance of quails on many occasions. This study was aimed to evaluate the effect of Piper betle L. (betel leaf) infuse supplementation on egg characteristics of quails. Quails were raised in Slamet Quail Farm, Sukabumi, West Java, Indonesia for 3 months. Quails had been fed adlibtum using a commercial diet. Betel leaf supplementation in different concentration had been given to replace drinking water. The treatments were P0: 0% supplementation, P1: 10% supplementation was given since day old quail (DOQ), P2: 20% supplementation was given since DOQ, P3: 30% supplementation was given since DOQ, P4: 10% supplementation was given since laying phase, P5: 20% supplementation was given since laying phase, P6: 30% supplementation was given since laying phase. The results showed that betel leaf infuse supplementation reduced the weight of egg shell, increasing the weight of egg albumin and increased egg weight significantly (P<0.05). There was no significant effect (P>0.05) on another egg quality variables. It could be concluded that betel leaf infuses supplementation could affect the egg shell, albumin, and egg weight without affecting other egg quality traits. Overall, betel leaf supplementation could be applicated because it could increase egg albumin quality and egg weight. Even though additional handling is needed because betle leaf infuses supplementation could reduce egg shell quality and the egg could break easily.